Acute exercise-induced muscle injury - McKune, A. J.; Semple, S. J.; Peters-Futre, E. M. (Biology of Sport, 2012)
While much research has recently been focussing on the chronic effects of overtraining, the acute damaging effects of individual eccentric exercise bouts on muscle remain of interest and underlie long-term training effects. Systemic markers of muscle damage are limited in terms of sensitivity and reliability. A clearer insight into the extent of the damage and mechanisms involved are being obtained from ultrastructural, functional and molecular examination of the muscle. There are currently indications that while the initial muscle damage may appear to have negative consequences in the short term, intense eccentric exercise appears to initiate a remodelling process and promote favourable adaptation of muscle following training, which has applications for promoting health, rehabilitation and sports performance.